Influencia de la productividad en la calidad del servicio de atención al cliente en la empresa DeLaborum Plus SAC del año 2017 - Martinez Gutierrez, Karen Elizabeth (2017)
The purpose of this paper is to offer an investigation on productivity and how it influences the quality of customer service according to the perspective collected from the employees that make up the customer service area of DeLaborum Plus SAC to measure its productivity, as well as the users to measure the level of quality of service. The following problem was addressed in the study: How does productivity influence the quality of the customer service of DeLaborum Plus SAC in 2017?. To determine it with reinforcement in the theoretical framework and using various techniques such as the survey, internet browsing and statistical tables that lead me to corroborate the hypothesis that productivity has a positive effect on the quality of customer service of the company DeLaborum Plus SAC of the year 2017. For the research into account at the productivity level, a sample universe of 11 collaborators and to measure the quality of service was carried out through a systematic sampling obtaining a sample of 110 users; Likewise, the survey was applied as a quantitative method to obtain results; from which it was evidenced that the degree of relationship is positive moderate between both variables, with a Spearman's Rho of (0.623) and a p - value = 0.000 <0.05, being highly significant at 1% of significance, concluding that: Productivity positively influences the quality of customer service of De Laborum Plus SAC. It was also determined that the productivity of employees is at a medium level with 55% and the quality of customer service at a low level with 55%. This is mainly determined that 45% of the employees do not agree that they receive adequate training, nor do they know exactly the procedures that are carried out daily to provide better care. which is perceived by the user, while 45% say that the staff is not trained to provide adequate care.